2016
DOI: 10.3389/fnmol.2016.00150
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Valproate Exposure Differentially Affects Parvalbumin-Expressing Neurons and Related Circuits in the Cortex and Striatum of Mice

Abstract: Autism spectrum disorders (ASD) comprise a number of heterogeneous neurodevelopmental diseases characterized by core behavioral symptoms in the domains of social interaction, language/communication and repetitive or stereotyped patterns of behavior. In utero exposure to valproic acid (VPA) has evolved as a highly recognized rodent ASD model due to the robust behavioral phenotype observed in the offspring and the proven construct-, face- and predictive validity of the model. The number of parvalbumin-immunoreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 106 publications
(151 reference statements)
7
68
1
2
Order By: Relevance
“…Intraperitoneal IPTG administration at days PND18, 21 and 24 induced the expression of the shPV22, which eventually led to an efficient downregulation of PV protein expression levels detected at PND25. Of importance for future behavioral experiments, PV levels after IPTG-mediated downregulation, as well as the distribution and staining intensities of PV + cells were similar to those observed in well-known ASD mouse models such as Shank3B −/− , VPA-exposed, Cntnap2 −/− and PV +/− mice (~50% of WT (see Schwaller et al, 2004;Wöhr et al, 2015;Filice et al, 2016;Lauber et al, 2016Lauber et al, , 2018). Moreover, strongly in support of the importance of the reversibility of shRNA-mediated PV downregulation, we had shown that the ASD-related phenotype in PV +/− mice (Wöhr et al, 2015) was attenuated following the upregulation of PV levels via estradiol (E2) administration during early postnatal development (Filice, Lauber, Vorckel, Wöhr, & Schwaller, 2018).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Intraperitoneal IPTG administration at days PND18, 21 and 24 induced the expression of the shPV22, which eventually led to an efficient downregulation of PV protein expression levels detected at PND25. Of importance for future behavioral experiments, PV levels after IPTG-mediated downregulation, as well as the distribution and staining intensities of PV + cells were similar to those observed in well-known ASD mouse models such as Shank3B −/− , VPA-exposed, Cntnap2 −/− and PV +/− mice (~50% of WT (see Schwaller et al, 2004;Wöhr et al, 2015;Filice et al, 2016;Lauber et al, 2016Lauber et al, , 2018). Moreover, strongly in support of the importance of the reversibility of shRNA-mediated PV downregulation, we had shown that the ASD-related phenotype in PV +/− mice (Wöhr et al, 2015) was attenuated following the upregulation of PV levels via estradiol (E2) administration during early postnatal development (Filice, Lauber, Vorckel, Wöhr, & Schwaller, 2018).…”
Section: Discussionsupporting
confidence: 61%
“…After having established IPTG‐induced downregulation of PV and Pvalb mRNA expression in fibroblasts (Figure ) and of PV protein levels in various brain regions from transgenic mice (Figure ), we investigated the distribution of PV + neurons in the brain of transgenic mice with a focus on the cortex, striatum and reticular thalamic nucleus (RTN). The former two regions were selected based on the reported decrease in PV expression in ASD mouse models including PV +/− , Shank1 −/− , Shank3B −/− and Cntnap2 −/− and in utero VPA‐exposed mice (Filice et al., ; Lauber, Filice, & Schwaller, , ). In control (untreated) transgenic mice, the typical laminar distribution of PV + cells, as well as the relative density of PV + neurons in the different cortical layers was observed (Figure ); the staining pattern was indistinguishable from the one reported before in many studies (e.g., fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using this approach, we have shown that in postnatal day (PND) 25 PV2/2 mice, Pvalb neurons are not absent-as could be deduced by the complete absence of PV immunoreactivity-but deficient of PV. Similar observations were made in PV1/2, Shank12/2, Shank3B2/2 (Filice, V€ orckel, Sungur, W€ ohr, & Schwaller, 2016), and in utero valproic acid (VPA)-exposed mice (Lauber, Filice, & Schwaller, 2016).…”
Section: Parvalbumin Neurons As a Hub In Autism Spectrum Disorderssupporting
confidence: 63%
“…Using this approach, we have shown that in postnatal day (PND) 25 PV−/− mice, Pvalb neurons are not absent—as could be deduced by the complete absence of PV immunoreactivity—but deficient of PV. Similar observations were made in PV+/−, Shank1−/−, Shank3B−/− (Filice, Vörckel, Sungur, Wöhr, & Schwaller, ), and in utero valproic acid (VPA)‐exposed mice (Lauber, Filice, & Schwaller, ). In all of these models, we observe lower numbers of PV‐immunoreactive cells and decreased PV protein (and Pvalb mRNA) levels compared to WT mice; however the number of VVA‐positive PNN‐ensheathed cells is unchanged, indicating that PV protein expression is strongly down‐regulated in Pvalb neurons of these genetic and environmental ASD mouse models (Figure ).…”
supporting
confidence: 65%
“…Furthermore, it has been shown that knockout of this gene affects spine density, glutamatergic receptor trafficking and perisomatic inhibition [73, 74]. In this sense, the pharmacological model of ASD based on prenatal exposure to valproate also showed a reduction of PV at the levels of protein, mRNA and cell number [75]. The BTBR mouse idiopathic model of ASD also has reduced GABAergic neurotransmission [76], as well as decreased levels of PV+ expression and PV+ contacts onto pyramidal cells in somatosensory cortex [71].…”
Section: Pre-clinical Models Of Asd and Ts With Interneuronal Alteratmentioning
confidence: 99%